Nano-size Polymers Preparation, Properties, Applications - Fakirov, Stoyko (Springer International Publishing : Imprint: Springer, 2016)
This book details all current techniques for converting bulk polymers into nano-size materials. The authors highlight various physical and chemical approaches for preparation of nano-size polymers. They describe the properties of these materials and their extensive potential commercial applications.